Multianalytical Method Validation for Qualitative and Quantitative Analysis of Solvents of Abuse in Oral Fluid by HS-GC/MS - Bruna Claudia Coppe; Bruna Tassi Borille; Taís Regina Fiorentin; Ana Laura Bemvenuti Jacques; Ana Claudia Fagundes; Stela Maris de Jezus Castro; Lysa Silveira Remy; Flavio Pechansky; Renata Pereira Limberger (International Journal of Analytical Chemistry)
The use of oral fluid as a biological matrix to monitor the use of drugs of abuse is a global trend because it presents several advantages and good correlation to the blood level. Thus, the present work aimed to develop and validate an analytical method for quantification and detection of solvents used as inhalants of abuse in oral fluid (OF), using Quantisal™ as collector device by headspace and gas chromatography coupled with a mass detector (HS-GC/MS). Chromatographic separation was performed with a ZB-BAC1 column and the total time of analysis was 11.8 min. The method showed good linearity (correlation coefficient higher than 0.99 for all solvents). The limits of detection ranged from 0.05 to 5 mg/L, while the lower limits of quantification ranged from 2.5 to 12.5 mg/L. Accuracy, precision, matrix effect, and residual effect presented satisfactory results, meeting the criteria accepted for the validation of bioanalytical methods. The method showed good selectivity considering that, for solvents coeluting at the same retention time, resolution was performed by the mass detector. The method developed proved to be adequate when applied in OF samples from users of drugs and may be used to monitor the abuse of inhalants in routine forensic analyses.